THE EFFECT OF THE USE OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) ON THE EXPLANATION TEXT ANALYSIS OF STUDENTS OF CLASS X1 SMA N 15 PADANG - Fathya Zahara; Trisna Helda; Wahyudi Rahmat (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research is motivated because students still have difficulties in learning to analyze expansion text. This study aims to describe the skills of Analyzing Explanatory Texts without and by using the Cooperative Integrated And Composition (CIRC) learning model towards the skills of Analyzing Text Exploration of Class X1 students of SMA N 15 Padang. This type of research is quantitative by using experimental methods. The design of this study is Postest Only Control Design. The population of this study was all students of class X1 of SMA N 15 Padang. The sample in this study were students of class X1 SMA N 15 Padang, amounting to 30 people in the experimental class and 26 in the control class. The data in this study are scores on the skills of analyzing explanatory texts without and by using Cooperative Integrated And Composition (CIRC) learning models. This research can be concluded as follows. First, the level of skills in Analyzing Text Expansion without using the Cooperative Integrated Reading and Composition (CIRC) model of class XI students of SMA N 15 Padang obtained an average score of 74.61 with a classification of 66-75% which is more than enough (LdC). Secondly, the level of skills in Analyzing Text Expansion using the Cooperative Integrated Reading and Composition (CIRC) model of class XI students of SMA N 15 Padang obtained an average score of 81.11 with a classification of 76- 85% which is good (B). Third, from the results of data analysis that has been carried out that the use of Cooperative Integrated Reading and Composition (CIRC) models can improve the skills of analyzing expansiasi text, it is seen that the alternative hypothesis (H1) is accepted at a significant level of 95% and dk = n-2 due to tcount > table (3.42> 1.67). AbstrakPenelitian ini dilatarbelakangi karena siswa masih mengalami kesulitan dalam belajar menganalisis teks ekspansi. Penelitian ini bertujuan untuk mendeskripsikan keterampilan Menganalisis Teks Eksplorasi tanpa dan dengan menggunakan model pembelajaran Cooperative Integrated And Composition (CIRC) terhadap keterampilan Menganalisis Teks Eksplorasi siswa kelas X1 SMA N 15 Padang. Jenis penelitian ini adalah kuantitatif dengan menggunakan metode eksperimen. Desain penelitian ini adalah Postest Only Control Design. Populasi penelitian ini adalah seluruh siswa kelas X1 SMA N 15 Padang. Sampel dalam penelitian ini adalah siswa kelas X1 SMA N 15 Padang yang berjumlah 30 orang di kelas eksperimen dan 26 orang di kelas kontrol. Data dalam penelitian ini berupa skor keterampilan menganalisis teks eksplanasi tanpa dan dengan menggunakan model pembelajaran Cooperative Integrated And Composition (CIRC). Hasil penelitian ini dapat disimpulkan sebagai berikut. Pertama, tingkat keterampilan Menganalisis Teks Ekspansi tanpa menggunakan model Cooperative Integrated Reading and Composition (CIRC) siswa kelas XI SMA N 15 Padang memperoleh skor rata-rata 74,61 dengan klasifikasi 66-75% sudah lebih dari cukup. (LdC). Kedua, tingkat keterampilan Menganalisis Teks Ekspansi dengan model Cooperative Integrated Reading and Composition (CIRC) siswa kelas XI SMA N 15 Padang memperoleh skor rata-rata 81,11 dengan klasifikasi 76-85% termasuk baik (B) . Ketiga, dari hasil analisis data yang telah dilakukan bahwa penggunaan model Cooperative Integrated Reading and Composition (CIRC) dapat meningkatkan keterampilan menganalisis teks ekspansiasi, terlihat bahwa hipotesis alternatif (H1) diterima secara signifikan. level 95% dan dk = n-2 karena thitung> tabel (3,42> 1,67).